Radiative heat transfer - Modest, M. F. (Elsevier Science, 2013)
The third edition of Radiative Heat Transfer describes the basic physics of radiation heat transfer. The book provides models, methodologies, and calculations essential in solving research problems in a variety of industries, including solar and nuclear energy, nanotechnology, biomedical, and environmental. Every chapter of Radiative Heat Transfer offers uncluttered nomenclature, numerous worked examples, and a large number of problems-many based on real world situations-making it ideal for classroom use as well as for self-study.
Keywords: Heat -- Transmission.; Heat -- Radiation and absorption.; Two-phase flow.; elektronické knihy; electronic books